Compact heat exchangers : analysis, design and optimization using FEM and CFD approach - Ranganayakulu, C. (Chennu); Seetharamu, K. N. (Wiley-ASME Press series., 2018)
A comprehensive source of generalized design data for most widely used fin surfaces in CHEs Compact Heat Exchanger Analysis, Design and Optimization: FEM and CFD Approach brings new concepts of design data generation numerically (which is more cost effective than generic design data) and can be used by design and practicing engineers more effectively. The numerical methods/techniques are introduced for estimation of performance deteriorations like flow non-uniformity, temperature non-uniformity, and longitudinal heat conduction effects using FEM in CHE unit level and Colburn j factors and Fanning friction f factors data generation method for various types of CHE fins using CFD. In addition, worked examples for single and two-phase flow CHEs are provided and the complete qualification tests are given for CHEs use in aerospace applications. Chapters cover: Basic Heat Transfer; Compact Heat Exchangers; Fundamentals of Finite Element and Finite Volume Methods; Finite Element Analysis of Compact Heat Exchangers; Generation of Design Data by CFD Analysis; Thermal and Mechanical Design of Compact Heat Exchanger; and Manufacturing and Qualification Testing of Compact Heat Exchanger. Provides complete information about basic design of Compact Heat Exchangers Design and data generation is based on numerical techniques such as FEM and CFD methods rather than experimental or analytical ones Intricate design aspects included, covering complete cycle of design, manufacturing, and qualification of a Compact Heat Exchanger Appendices on basic essential fluid properties, metal characteristics, and derivation of Fourier series mathematical equation Compact Heat Exchanger Analysis, Design and Optimization: FEM and CFD Approach is ideal for senior undergraduate and graduate students studying equipment design and heat exchanger design.